Investigation of hexamethylenetetramine effects on formation and corrosion resistance of anodic coatings developed on AZ31B alloys - Miao, Xi; Shi, Xiaoting; Shen, Youliang; Zhang, Wenxia; Hu, Wenxin; Zhang, Shufang; Huang, Xiwen; Wang, Yu; Zhao, Rongfang; Zhang, Rongfa (Surface & coatings technology, 2022)
To fabricate calcium-phosphate (CaP) coatings with good corrosion resistance on AZ31B alloys via micro-arc oxidation (MAO) treatment, hexamethylenetetramine (HTMA) was selected as an effective MAO additive of magnesium alloys. The influences of HTMA concentrations on formation mechanism and coating property were systematically investigated in a near-neutral base solution composed of NH4HF2, EDTA-CaNa2, phytic acid and phosphoric acid. The results show that HTMA can increase the solubility of calcium salts and significantly promote the formation of MAO coatings on AZ31B alloys. In a base solution with 360 g/L HTMA, the fabricated MAO sample achieves the best corrosion resistance in Hank's solution and the corrosion current density (icorr) is significantly decreased by two orders of magnitude than that treated in solution without HTMA. During MAO treatment, acting as an effective corrosion inhibitor of magnesium alloys, HTMA is helpful for coating formation via protecting the magnesium sample from corrosion. In 3.5 % NaCl solution with different HTMA concentrations, the maximum inhibition efficiency is 94.57 % at a HTMA concentration of 360 g/L. Moreover, HTMA molecules are absorbed on the surface of AZ31B alloys following the Langmuir absorption isotherm in the range of 120 to 360 g/L, however, excessively high concentrations fail to conform with the equation, which may be attributed to steric hindrance. •HTMA can increase the solubility of calcium salts.•HTMA significantly promotes the formation of MAO coatings on AZ31B alloys.•HTMA is an effective inhibitor of Mg alloys.•HTMA molecules are absorbed following Langmuir absorption isotherm in the range of 120 to 360 g/L.•The MAO sample fabricated in the solution with 360 g/L HTMA achieves the best corrosion resistance.